2004
DOI: 10.1002/hec.911
|View full text |Cite
|
Sign up to set email alerts
|

Valuation of the risk of SARS in Taiwan

Abstract: Two surveys conducted in Taiwan during the spring 2003 severe acute respiratory syndrome (SARS) epidemic reveal a high degree of concern about the threat posed by SARS to Taiwan and its residents, although respondents believe they are knowledgeable about the risk of SARS and that it is susceptible to individual control. Willingness to pay (WTP) to reduce the risk of infection and death from SARS is elicited using contingent valuation methods. Estimated WTP is high, implying values per statistical life of US$3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
68
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 22 publications
3
68
0
1
Order By: Relevance
“…Thus, neither the risk perception score nor its individual components seemed to affect preventative actions, apart from the likelihood of avoiding public transportation. Liu et al ( 19 ) found different components of risk perception to be significant in different geographic areas. In the Netherlands, higher risk perception was associated with more self-reported precautionary actions for SARS; however, when other explanatory variables like age, sex, education were included, no significant association between risk perception and precautionary actions was observed ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, neither the risk perception score nor its individual components seemed to affect preventative actions, apart from the likelihood of avoiding public transportation. Liu et al ( 19 ) found different components of risk perception to be significant in different geographic areas. In the Netherlands, higher risk perception was associated with more self-reported precautionary actions for SARS; however, when other explanatory variables like age, sex, education were included, no significant association between risk perception and precautionary actions was observed ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, estimates have been based on extrapolation from estimates for higher-income countries but these are subject to substantial uncertainties about the appropriate adjustments for differences in income, economic structure, and other factors (e.g., Chestnut et al 1997;Stevens et al 2005). Recently, several stated-preference estimates have become available (e.g., Hammitt and Liu 2004;Liu et al 2005;Hammitt and Zhou 2006;Wang and Mullahy 2006) but stated-preference estimates are often viewed as less reliable than wage-differential and other revealed-preference estimates.…”
mentioning
confidence: 97%
“…The potential net benefits of a national vaccination program should be even greater, essentially because the vaccine costs can be further reduced through government mass purchasing power. The estimated VSL in this study was within the prior wage‐differential and CV estimate ranges in Taiwan [8,24–27]. Thus, our estimated VSL is potentially applicable for reference purposes in cost‐benefit analyses aimed at assessing the potential lives saved by national HPV vaccination programs.…”
Section: Discussionmentioning
confidence: 53%
“…The WTP for a hypothetical HPV vaccine was quite high compared with several CVM studies on vaccination interventions in Taiwanese setting [7–10]. According to the prior studies, the characteristics of the target disease, in terms of speed of progression [24], oncogenic disease [24] or degree of severity [11,22,23] were positively related to WTP.…”
Section: Discussionmentioning
confidence: 96%